Towards a Circular Blue Economy in the Global South: Potentials and Challenges in Kiribati - Ketaren, Emma Seruni; Andi Faradilla Ayu Lestari (Journal of World Trade Studies, 2023)
Countries with large ocean areas tend to rely on aquaculture products to drive their economy, such as Kiribati which relies heavily on the fisheries sector because its ocean area is significantly larger than its land area. To claim that the sea is Kiribati's only hope for its economy is not an exaggeration given how much aquaculture products contribute to its national income. Unfortunately, Kiribati's heavy reliance on the fisheries sector is not balanced with an adequate management framework and this condition is increasingly exacerbated by climate change and over-exploitation of marine resources, which are posing serious threats to Kiribati's economy. Using descriptive qualitative methods, this research aims to identify sectors with potential as new economic sources and challenges for the development of a blue circular economy in Kiribati. The findings of this research will reveal that Kiribati has several sectors that can be utilized in the implementation of a circular blue economy. However, numerous challenges prevent these sectors from reaching their full potential. Furthermore, this research will aim to formulate policy recommendations to maximize Kiribati's circular blue economy potentials.